Revisiting Variance Decomposition when Independent Samples Intersect - Tillé, Yves; Vallée, Audrey-Anne (My University, 2017)
The variance and the estimated variance of the expanded estimator in the intersection of two independent samples can be decomposed into two ways. Due to the inclusion probabilities, it is generally more practical to compute the variance with one decomposition. With the other one, it is more convenient to estimate the variance.
Keywords: everse approachTwo-phase samplingTwo-stage samplingVariance estimation